Comportamento espaço temporal: um estudo das ferramentas tecnológicas para a gestão do turismo inteligente - Sturmer, Carlos Rogério (2022)
Displacement, space and time are elements present in the tourist phenomenon. In this perspective, there are numerous works that deal with tourist displacement and issues of space and time, however, most of them in macro-spatial scope, focus on international displacements and the impacts of mass tourism. Therefore, it is necessary to use new technologies for counting and monitoring people in the space-time context in tourist destinations within the municipality, as well as the importance of choosing, defining and using indicators that allow monitoring the evolution in addition to pointing out strategies. more efficient for the development and improvement of these places, allowing decisionmaking for both public and private managers, thus creating an innovative, sustainable and technological management for these destinations. What was sought was to study the spatiotemporal behavior on a microscale, that is, a cut of municipal coverage. In this way, this work tried to answer the following question, how can people monitoring tools contribute to the understanding of displacement and counting of people within the tourist destination? Method: For the development of this work, a systematic review was carried out taking into account the scientific publications in the ACM, IEEE, Science Direct and Scopus databases in the last five years, where the most relevant publications on the subject were sought, which pointed out the five technologies most used by the authors. The choice of counting and tracking technology using Wi-Fi was due to the fact that it stands out in the review, as it is a new, low-cost technology and can be used IoT sensors. A prototype was built to test data collection using an ESP8266 board with built-in Wi-Fi. The first test was carried out over a period of two months at the International Bus Station of Foz do Iguaçu and later new collectors were installed in different places in the city that would allow analyzing a possible triangulation between them. Results: The test of the collector prototype in the intervention was successful in relation to the collection of MAC addresses of the devices that appeared in the place within the period, allowing sampling of the devices in the place at a certain time, day, month and year, proving that the prototype reading is reliable. The second experiment carried out in different locations identified the passage at several points of the same MAC address, enabling its triangulation. The construction of its own portal allowed the visualization of data on the spatiotemporal behavior of tourists in real time. Conclusion: The study pointed out the main technologies used for monitoring people and the prototype tests brought promising results. The technology used proved to be effective for counting and tracking devices in a given location and subsequently triangulating them. The results obtained can still be improved with new implementations, functions or technologies added to it along with the improvements of the developed portal, thus contributing to the management of tourist destinations through an innovative tool for tracking tourists.